POTENSI PUISI INDONESIA SEBAGAI MEDIA BIBLIOTERAPI KESEHATAN MENTAL - Agustiningsih, Dheka Dwi; Nurhadi, Jatmika (STKIP Siliwangi, 2024)
This study analyzes three Indonesian poems—Dengan Puisi, Aku by Taufiq Ismail, Episode by W.S. Rendra, and Cipasung by Acep Zamzam Noor—within the framework of literary psychology to explore their potential as therapeutic tools for mental health. The analysis employs nine criteria derived from the theories of Leedy (1969) and Mazza (2022), focusing on aspects such as theme, language, emotional depth, structure, cultural relevance, interpretive flexibility, complexity balance, and positive and transformative themes. The results demonstrate that these poems consistently support positive emotional reflection and responsibility, aligning with the study's objective to explore the therapeutic potential of Indonesian poetry. These poems avoid themes that could exacerbate mental health issues, such as despair, guilt, and suicidal tendencies, making them relevant and effective for use in mental health therapy in Indonesia. This research contributes significantly to the literature on poetry therapy by introducing a literary psychology approach to analyzing Indonesian poetry. The findings not only enhance the understanding of how poetry can aid emotional healing but also provide a foundation for developing culturally relevant and effective therapeutic methods in Indonesia.